Bioinformatics-based analysis and experimental validation of PANoptosis-related biomarkers and immune infiltration in diabetic nephropathy - Zhang, Su; Zhang, Yun; Hu, Weitao; Huang, Chunyan; Zhang, Yifang; Chen, Xiaoqing (Frontiers in Endocrinology, 2025)
BackgroundDiabetic nephropathy (DN) is a frequent and serious microvascular complication of diabetes. PANoptosis is a novel mode of cell death that encompasses apoptosis, necrosis and pyroptosis. However, effective PANoptosis-related biomarkers for DN are currently lacking. Therefore, this study aimed to elucidate the role of PANoptosis-related genes (PRGs) in the development of DN and their potential as diagnostic markers of DN, as well as their association with immune cell infiltration.Materials and methodsWe retrieved the DN-related dataset GSE30122 from the GEO database. Then differentially expressed genes (DEGs) were identified and DEGs were analyzed for functional enrichment. In addition, we obtained key gene modules by WGCNA. Subsequently, we gained the intersecting genes of DEGs, key gene modules and PRGs. Four algorithms were further used to screen the key DE-PRGs in DN (DNDE-PRGs). We also investigated the biological functions of the key DNDE-PRGs by GSEA software. Furthermore, we analyzed the immune infiltration of DN tissues. The correlation of key genes with glomerular filtration rate (GFR) and blood urea nitrogen (BUN) was also examined. Finally, key genes were validated using clinical samples and db/db mice.ResultsWe identified two key DNDE-PRGs (AKT3 and FYN). They showed good diagnostic value in the DN. And they were associated with immune cell infiltration. In addition, they have a correlation with GFR and BUN. Finally, they were validated in clinical samples and animal experiments.ConclusionAKT3 and FYN may be good PANoptosis-related biomarkers in DN. This provides new insights into the pathogenesis of DN.